¿Es la justicia como equidad una exigencia moral universalizable? - Tubino Mongilardi, Fidel (Pontificia Universidad Católica del Perú. Instituto Riva Agüero, 2015)
This paper aims to “demonstrate” that whereas man does not have a universalized conceptionof justice based on intercultural consensus, he must seek it dialogically. Nowadays, themulticultural nature of society requires rules to ensure reasonable coexistence among individuals.To achieve this goal, it is necessary to have a consensual conception of justice thatprovides criteria for dialogue and intergroup coexistence.